Triacontanol and Its Second Messenger 9-β-l(+)-Adenosine as Plant Growth Substances - Ries, Stanley (1991)
Triacontanol (TRIA), a common constituent of plant waxes, was first shown in 1977 to be an active growth substance which at nanomolar concentrations increased the growth and yield of crops. TRIA is used to increase crop yields on millions of hectares, particularly in Asia. Many investigators have shown that it affects several basic metabolic processes including photosynthesis, nutrient uptake, and enzyme activity. However, the initial site of action has not been elucidated. TRIA rapidly elicits a second messenger (TRIM) in rice (Oryza sativa L.), which at nanomolar concentrations causes plants to respond in a manner similar to TRIA. TRIM has been identified as 9-β-l(+)-adenosine (9H-purin-6-amine, 9-β-l-ribofuranosyl). During the process of isolating and identifying 9-β-l(+)-adenosine, it was shown that this enantiomer, which previously has not been reported as occurring in nature, made up about 1% of the total adenosine pool in roots from untreated rice seedlings.